Penerapan E-government di Kabupaten Malang Tinjauan Elemen Sukses Manajemen Proyek - Wahyu Candra Setyaji; Siti Aisyah; Anisa Hudi Widaningrum (Telkom University, 2026)
Digital transformation through electronic government has now become a strategic step for local governments to realize bureaucratic governance that is transparent, accountable, and responsive to public needs. Malang Regency has responded to this global demand through various service innovations, but implementation on the ground often faces multidimensional challenges, ranging from infrastructure gaps to human resource readiness. This study aims to map the implementation of e-government in Malang Regency and comprehensively analyze the determinant factors of project management success that affect its sustainability. This study uses the Systematic Literature Review (SLR) method, guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) standard reporting protocol, to critically examine 21 selected journal articles. Research findings indicate that the digital ecosystem has been extensively implemented in critical sectors, including judicial administration, integrated healthcare services, populationadministration, and business licensing. In-depth analysis identifies three main pillars of project success: Support (strong commitment from local leaders and consistent regulations), Capacity (reliability of technological infrastructure and technical competence of officials), and Value (quality of information, service time efficiency, and user satisfaction). This study provides practical implications that the Malang Regency Government should prioritize the standardization of data integration across departments and develop continuous technical training curricula for village officials to address the capacity gaps found. The study recommends adopting an adaptive project management framework to ensure the sustainability of regional digital transformation.